Cued by What We See and Hear: Spatial Reference Frame Use in Language - Coventry, Kenny R.; Andonova, Elena; Tenbrink, Thora; Gudde, Harmen B.; Engelhardt, Paul E. (Frontiers in Psychology, 2018)
To what extent is the choice of what to say driven by seemingly irrelevant cues in the visual world being described? Among such cues, how does prior description affect how we process spatial scenes? When people describe where objects are located their use of spatial language is often associated with a choice of reference frame. Two experiments employing between-participants designs (N=490) examined the effects of visual cueing and previous description on reference frame choice as reflected in spatial prepositions (in front of, to the left of, etc.) to describe pictures of object pairs. Experiment 1 examined the effects of visual and linguistic cues on spatial description choice through movement of object(s) in spatial scenes, showing sizeable effects of visual cueing on reference frame choice. Experiment 2 monitored eye movements of participants following a linguistic example description, revealing two findings: eye movement “signatures” associated with distinct reference frames as expressed in language, and transfer of these eye movement patterns just prior to spatial description for different (later) picture descriptions. Both verbal description and visual cueing similarly influence language production choice through manipulation of visual attention, suggesting a unified theory of constraints affecting spatial language choice.